2022
DOI: 10.3390/antiox11061054
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Ameliorates the Negative Effect of Osmotic Stress in Human and Bovine Ovarian Stromal Cells

Abstract: Ovarian tissue cryopreservation transplantation (OTCT) is the most flexible option to preserve fertility in women and children with cancer. However, OTCT is associated with follicle loss and an accompanying short lifespan of the grafts. Cryopreservation-induced damage could be due to cryoprotective agent (CPA) toxicity and osmotic shock. Therefore, one way to avoid this damage is to maintain the cell volume within osmotic tolerance limits (OTLs). Here, we aimed to determine, for the first time, the OTLs of ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…Once the oxidases and antioxidant enzymes are out of balance, a large amount of ROS will be produced, causing oxidative stress and damaging tissues [8]. According to research, on bovine ovarian stromal cells, MLT may lessen the adverse consequences of osmotic pressure by increasing the protein expression of CAT and SOD (Asadi et al., 2022). This aligns with the findings of our research.…”
Section: Discussionmentioning
confidence: 99%
“…Once the oxidases and antioxidant enzymes are out of balance, a large amount of ROS will be produced, causing oxidative stress and damaging tissues [8]. According to research, on bovine ovarian stromal cells, MLT may lessen the adverse consequences of osmotic pressure by increasing the protein expression of CAT and SOD (Asadi et al., 2022). This aligns with the findings of our research.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Wang et al (2011) found accumulated osmotic damage was temperature specific while Williams & Takahashi (1982) found membrane lysis of sea urchin eggs was mitigated at lower temperatures during hypertonic challenge. Supplements that prevent membrane and cytoskeletal regulation may reduce time-dependent osmotic damage ( Asadi, Najafi & Benson, 2022 ). However, there may be a trade-off between time-dependent osmotic damage and sensitivity to lysis during osmotic challenge, or loss of cell functionality with supplements that depolarizes F-actin, such as cytochalasin-D or cytochalasin-B ( Fujihira, Kishida & Fukui, 2004 ; Takamatsu et al, 2005 ; Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, POF has a significant effect on the reproductive health and quality of life of women. Current research suggests that the primary cause of POF is low ovarian reserve function due to atresia of the dominant follicles and failure of the primordial follicles in the ovary due to oxidative stress (Sun et al 2018, Asadi et al 2022, Jiang et al 2019. GCs play a crucial role in follicular development and maturation by producing estradiol and other maturation-promoting factors (Zhu et al 2022).…”
Section: Introductionmentioning
confidence: 99%